Application of response surface methodology in preparation of reduced-fat paneer from recombined milk - Chaudhari, Mahesh; Pinto, Suneeta; Dharaiya, Chetan N; Patel, Sunil (Indian Journal of Dairy Science, 2023)
The objective of current study was to optimize the level of milk fat, milk SNF (MSNF) and whey protein concentrate – 80 (WPC) to prepare low-fat paneer from recombined milk using response surface methodology. Milk fat, MSNF and WPC were used as variables while sensory attributes of paneer viz., flavour, body & texture, colour & appearance and overall acceptability, as well as compositional characteristics viz., moisture content and fat on dry matter basis were used as responses. On the basis of the results, RSM suggested the levels of milk fat, MSNF and WPC to be 2.14%, 10.72% and 0.75% respectively with desirability of 0.92. The experimental paneer was prepared as per the suggestions from RSM and compared with control paneer prepared from standardized milk containing 4.5% milk fat and 8.5% MSNF. The chemical composition of experimental paneer was significantly different from control paneer while rheological and sensory characteristics were statistically similar. Hence, RSM can be a useful tool for optimization of low-fat recombined milk paneer.